PENGARUH PENAMBAHAN BENZILADENIN PADA PELAPIS KITOSAN TERHADAP MUTU DAN MASA SIMPAN BUAH JAMBU BIJI ‘CRYSTAL’ - Soesiladi Esti Widodo; Zulferiyenni Zulferiyenni; Dian Wahyu Kusuma (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2013)
Guava ‘Crystal’ is one of the leading export product of guava. Postharvest problem that occur on guava ‘Crystal’ is the rapid process of ripening and the development of brown spots, so the shelf-life is shorter and causes a decrease in fruit qualities. Damage to fruit can be solved by soaking the fruit in a solution or by coating the fruit, so the rate of respiration and transpiration can be slowed. The material used for soaking the fruit was a plant growth regulators of benziladenine (BA). This research was aimmed at (1) studying the effects of the addition of BA into chitosan coating on the quality and shelf-life of guava ‘Crystal’, and (2) obtaining the best concentration of BA added to the chitosan coating to maintain the quality and prolong the shelf-life of guava ‘Crystal’. The results showed that (1) the addition of 2.5% chitosan coating was significantly able to prolong the fruit shelf-life of guava ‘Crystal’ of 2.83 and 6.12 days longer than control and acetic acid 0.5%, (2) the addition of BA concentrations of 25, 50 and 100 ppm shortened significantly the fruit shelf-life of guava ‘Crystal’, but did not influence its qualities, and (3) the using of 0.5% acetic acid as a solvent in 2.5% chitosan did not cause a bad affect, but soaking in 0.5% acetic acid as a main solution adversely affected the fruit qualities and shelf-life of guava ‘Crystal’.